Lichens are more tolerant against winter warming stress than vascular and non-vascular plants: Insights from an alpine field experiment - Finne, Eirik Aasmo; Bjerke, Jarle W.; Stordal, Frode; Tallaksen, Lena M. (Journal of Ecology, 2025)
1. Extreme weather events influence carbon cycling and lead to pervasive changes in ecosystem structure and function. Vegetation at high latitudes and in alpine bioclimatic zones can be particularly sensitive to winter warming events, which are short-lived climatic events where temperatures are unusually high and often include rainfall. With climate change the frequency and severity of winter warming events are increasing. 2. We report here from a field experiment on a lichen-dominated ridge at a high mountain plateau in central Norway. This is a common vegetation type at high latitudes and altitudes, yet little is known about ecophysiological responses to winter warming events in lichens, and how it may differ from responses in bryophytes and vascular plants. We ran a week-long simulation of vegetation stress from winter warming events through thaw–freeze and ice encasement, during late winter in 2021 and 2022. 3. The thaw–freeze treatment had minor effects on summer ecophysiology in lichens (Cladonia mitis, Cetraria islandica and Nephromopsis nivalis), while the species N. nivalis and to a lesser extent, C. mitis had reduced vitality after the ice encasement treatment. Contrastingly, the bryophyte Polytrichum juniperinum, and vascular plant Empetrum nigrum had reduced photosynthetic efficiency and seasonal growth in both thaw–freeze and ice encasement treatments. The ice encasement treatment was overall more lethal and led to reduced NDVI (Normalised Difference Vegetation Index). However, reduction in vitality of vascular and non-vascular plants was not enough to impact overall ecosystem carbon flux. 4. Synthesis: The lichen's stronger tolerance against thaw–freeze and ice encasement than co-existing plants oppose the general effects of summer climate warming, where lichens may succumb under greater plant-growth and warmer soils. This study advocates for the importance of year-round ecology to understand vegetation change under climate change.